Combined Blockade of Src Kinase and Epidermal Growth Factor Receptor with Gemcitabine Overcomes STAT3-Mediated Resistance of Inhibition of Pancreatic Tumor Growth - Nagaraj, Nagathihalli S. (2011)
PURPOSE: We previously established a mechanistic rationale for Src inhibition as a novel therapeutic target in pancreatic cancer and have shown that activated STAT3 is a biomarker of resistance to Src inhibition. The purpose of this study was to translate the current understanding of complementary activated tyrosine kinase signaling pathways by targeting Src kinase and epidermal growth factor receptor (EGFR). EXPERIMENTAL DESIGN: IC(50) values for dasatinib, a Src kinase inhibitor, erlotinib, an EGFR tyrosine kinase inhibitor and gemcitabine were determined and sensitive and resistant pancreatic cancer cell lines were identified. The in vitro and in vivo effects of these agents on multiple signaling pathways and tumorigenicity in pancreatic cancer were investigated. RESULTS: The combination of dasatinib, erlotinib and gemcitabine resulted in cooperative inhibition of cell migration and invasion of both sensitive and resistant pancreatic cancer cells as well as cooperative inhibition of multiple signaling pathways including FAK, AKT, ERK, JNK, MAPK and STAT3 at concentrations that were ineffective as individual agents or as double combinations of agents. The triple combination of agents was also most effective at inhibiting the growth of xenografts of both sensitive and resistant pancreatic cancer cells in vivo without increasing toxicity. Furthermore, combined inhibition of Src and EGFR with gemcitabine inhibited constitutively activated STAT3 in vitro and in vivo. CONCLUSIONS: These results provide evidence that combined targeted biological therapy in addition to cytotoxic chemotherapy can overcome treatment resistance. Such treatment strategies may be used to tailor therapy based on identified biomarkers of resistance to targeted monotherapy.